Drought stress responses in wild and cultivated Aspalathus linearis of the Suid Bokkeveld, Northern Cape Province of South Africa : linkages between local knowledge and empirical evidence - Rafferty, Melandri Crystal Tameron (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScConsEcol)--Stellenbosch University, 2018.